(untitled) (Analysis in Theory and Applications, 2012)
In this paper, some weighted estimates for the multivariate Hausdorff operators are obtained. It is proved that the multivariate Hausdorff operators are bounded on L^p spaces with power weights, which is based on the boundedness of multivariate Hausdorff operators on Herz spaces, and are bounded on weighted L^p spaces with the weights satisfying the homogeneity of degree zero.